(untitled) (Italian Review of Legal History, 2023)
International jurisprudence has a crucial role in the development of international environmental law. There is a close relationship between legal cases and environmental protection in international environmental law. Legal cases address contemporary problems and include new legal principles and rules of international law that can develop the scope (principles, structures and implementation) of environmental protection. In this perspective, judgments, advisory opinions and decisions of the international courts and tribunals, especially the International Court of Justice, have shown that State sovereignty has always been a limitation of the global expansion of environmental protection scope. Moving from absolute State sovereignty to the rule-based equitable and reasonable use of land could be an excellent opportunity to develop this legal field. Environmental protection emerged in the Trail Smelter case of 1941 as an earlier environmental dispute which resulted in the development of the environmental protection concept in other legal cases. Based on selected cases in international environmental law, the research attempts to analyze three stages of the emergence, enhancement and evolution of the environmental protection principle.